Case Report: Posterior Uveitis after Divalent Human Papillomavirus Vaccination in an Asian Female. Issue 6 (June 2020) - Ye, Hongfei; Feng, Huazhang; Zhao, Peiquan; Fei, Ping
Abstract : SIGNIFICANCE: Vaccine-associated uveitis has appeared in recent years because of various vaccines, whereas cases for human papillomavirus (HPV) vaccination were rarely reported. With more and more females becoming aware of its importance and choosing HPV vaccination, much more attention should be paid on the adverse effects of it. PURPOSE: The purpose of this study was to report a rare case of posterior uveitis after divalent HPV vaccination in an Asian female. CASE REPORT: A 29-year-old woman presented with acute vision loss accompanied by symptoms of headache, tinnitus, and myalgia after the third injection of HPV vaccination. The best-corrected visual acuity dropped to 20/500 for both eyes, and optical coherence tomography revealed bilateral multifocal submacular fluid. A short course of oral prednisone as well as Ozurdex intravitreal injection resulted in the reversal of all signs and symptoms. CONCLUSIONS: Although this case resembled Harada disease, we diagnosed it as vaccine-induced uveitis rather than coincidental autoimmune disease based on the rapid response to a short course of systemic corticosteroids. Because vaccine-induced uveitis is rare and difficult to distinguish from coincidental autoimmune disease, our case reminds eye care providers to be aware of the possible association between vaccination and a Harada-like reaction and to ask appropriately directed questions when obtaining history from young patients with uveitis. Based on this case, we also suggest Ozurdex intravitreal injection as a potential therapeutic choice, especially for patients with contraindication or personal concern to systemic corticosteroid.